DPP-4 inhibitor treatment: β-cell response but not HbA1c reduction is dependent on the duration of diabetes - Kozlovski P; Bhosekar V; Foley JE (Vascular Health and Risk Management, 2017)
Plamen Kozlovski,1 Vaishali Bhosekar,2 James E Foley3 1Novartis Pharma AG, Basel, Switzerland; 2Novartis Healthcare Private Limited, Hyderabad, India; 3Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA Introduction: Dipeptidyl peptidase-4 (DPP-4) inhibitors reduce hyperglycemia in patients with type 2 diabetes mellitus (T2DM) by enhancing insulin and suppressing glucagon secretion. Since T2DM is associated with progressive loss of β-cell function, we hypothesized that the DPP-4 inhibitor action to improve β-cell function would be attenuated with longer duration of T2DM.Methods: Data from six randomized, placebo-controlled trials of 24 weeks duration, where β-cell response to vildagliptin 50 mg twice daily was assessed, were pooled. In each study, the insulin secretory rate relative to glucose (ISR/G 0–2h) during glucose load (standard meal or oral glucose tolerance test) was assessed at baseline and end of study. The mean placebo-subtracted difference (PSD) in the change in ISR/G 0–2h from baseline for each study was evaluated as a function of age, duration of T2DM, baseline ISR/G 0–2h, glycated hemoglobin (HbA1c), fasting plasma glucose, body mass index, and mean PSD in the change in HbA1c from baseline, using univariate model.Results: There was a strong negative association between the PSD in the change from baseline in ISR/G 0–2h and duration of T2DM (r= −0.89, p<0.02). However, there was no association between the PSD in the change from baseline in ISR/G 0–2h and the PSD in the change from baseline in HbA1c (r=0.33, p=0.52). None of the other characteristics were significantly associated with mean PSD change in ISR/G 0–2h.Conclusion: These findings indicate that the response of the β-cell, but not the HbA1c reduction, with vildagliptin is dependent on duration of T2DM. Further, it can be speculated that glucagon suppression may become the predominant mechanism via which glycemic control is improved when treatment with a DPP-4 inhibitor, such as vildagliptin, is initiated late in the natural course of T2DM. Keywords: insulin, insulin secretion rate, glucagon, α-cell, β-cell, glucagon-like peptide 1, gastric inhibitory polypeptide